Influencing User Attention Using Real-Time Stylised Rendering - DINGLIANA, JOHN LALZOLIANA (My University, 2009)
In this paper, we present a series of experiments that were conducted to determine how using adaptive levels of artistic abstraction within an interactive 3D scene can influence user gaze behaviour. We found that when an object was placed in the center of stylised focus, users took significantly less time to complete a search and recognition task in comparison to normal renderings or when the target object was heavily abstracted i.e. stylistically out-of-focus. We also compared a number of different abstraction techniques and found that some abstraction styles consistently lead to faster search times than others. Finally we performed experiments using an eye-tracker to show that our real-time abstraction techniques can successfully draw user attention to specific objects within an interactive scene. We believe that our experimental framework will be useful in the future for comparing the effectiveness of different NPR styles in influencing a user?s perception of a scene.
TPCG 2009: Theory and Practice of Computer Graphics
PUBLISHED
Cardiff, UK
Keywords: Computer Graphics; Nonphotorealistic Rendering; Visualisation; Real-time; Computer Graphics